Planetology Future Explorations - Palaszewski, Bryan (IntechOpen, 2020)
Over the last 80 years, dreamers, engineers, mission planners, and scientists have sought, defined, and created many methods of exploring the solar system. Robotic missions to nearly every type of solar system object have been conducted. The data from these missions has opened new vistas on the riches of the planets and the asteroids. Water and other materials that can help humans survive in space have been found in abundance. Human lunar missions have returned with hundreds of kilograms of rocky and dusty samples. These samples (regolith) has given us hope that humanity will one day colonize the Moon, Mars, and the moons of other planets. Many space agencies around the world have shared their information and created collaborations for the betterment of all. Interplanetary dreams are part of humanity's future, those dreams will create a future where humanity can begin to flourish throughout the planets. This book is a celebration of those dreams.